Tag-SNPs in Phospholipase-Related Genes Modify the Susceptibility to Nephrosclerosis and its Associated Cardiovascular Risk - González, Luz M.; Robles, Nicolás R.; Mota-Zamorano, Sonia; Arévalo-Lorido, José C.; Valdivielso, José Manuel; López-Gómez, Juan; Gervasini, Guillermo (Frontiers in Pharmacology, 2022)
Nephrosclerosis patients have a high cardiovascular (CV) risk that is very often of more concern than the renal disease itself. We aimed to determine whether variants in phospholipase-related genes, associated with atherosclerosis and CV outcomes in the general population, could constitute biomarkers of nephrosclerosis and/or its associated CV risk. We screened 1209 nephrosclerosis patients and controls for 86 tag-SNPs that were identified in the SCARB1, PLA2G4A and PLA2G7 gene loci. Regression models were utilized to evaluate their effect on several clinical parameters. Most notably, rs10846744 and rs838880 in SCARB1 showed significant odds ratios (OR) of 0.66 (0.51-0.87), p=0.003 and 1.48 (1.11-1.96), p=0.007 for nephrosclerosis risk. PLA2G4A and PLA2G7 harboured several SNPs associated with atherosclerosis measurements in the patients, namely common carotid intima media thickness (ccIMT), presence of plaques, number of plaques detected and 2-year ccIMT progression (significant p-values ranging from 0.0004 to 0.047). Eight SNPs in PLA2G4A were independent risk factors for CV events in nephrosclerosis patients. Their addition to a ROC model containing classic risk factors significantly improved its predictive power from AUC=69.1%(61.4-76.9) to AUC=79.1%(73.1-85.1%), p=0.047. Finally, PLA2G4A rs932476AA and rs6683619AA genotypes were associated with lower CV event-free survival after controlling for confounding variables [49.59 (47.97-51.21) vs. 51.81 (49.93-51.78) months, p=0.041 and 46.46 (41.00-51.92) vs. 51.17 (50.25-52.08) months, p=0.022, respectively]. Variability in phospholipase-related genes play a relevant role in nephrosclerosis and associated atherosclerosis measurements and CV events.